2003
DOI: 10.1002/cbf.1059
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the ultrastructural neutrophil changes in alloxan‐induced diabetes in rats: response to a chemotactic challenge

Abstract: Experimental diabetes is one of the most popular conditions in which to study the relation between neutrophil leukocyte activity and periodontal destruction. The aetiology of neutrophil dysfunction in the gingival tissue associated with diabetes has yet to be clarified. Diabetes in rats decreases neutrophil chemotactic activity in proportion to the severity of this systemic disorder. The present study was carried out to evaluate the relationship between the severity of diabetes and the neutrophil response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The hyperglycemic environment in diabetes leads to a variety of cellular alterations 13 . Impaired neutrophil function has been detected in diabetic patients and in rodent models 62,69,72,95‐98 . Proliferation and differentiation of periodontal osteoblasts are downregulated in diabetic rats, which was confirmed in in vitro experiments with human osteoblasts 77,99,100 .…”
Section: Effect Of Diabetes In the Periodontium Of Humans And Rodentsmentioning
confidence: 74%
See 2 more Smart Citations
“…The hyperglycemic environment in diabetes leads to a variety of cellular alterations 13 . Impaired neutrophil function has been detected in diabetic patients and in rodent models 62,69,72,95‐98 . Proliferation and differentiation of periodontal osteoblasts are downregulated in diabetic rats, which was confirmed in in vitro experiments with human osteoblasts 77,99,100 .…”
Section: Effect Of Diabetes In the Periodontium Of Humans And Rodentsmentioning
confidence: 74%
“…Chemically induced type 1 diabetes (with alloxan or STZ) has been the most frequently used model, probably because of its low cost and the ease and rapidity of achieving diabetic animals. A large number of investigations 49,51‐81 indicated that alloxan‐ and STZ‐treated rodents had more severe spontaneous and induced periodontitis than non‐diabetic controls. In addition to the drug‐induced type 1 diabetes models, the genetically type 1 diabetic NOD mouse has been used in a periodontitis study 82 .…”
Section: Rodent Models Of Diabetes and Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…In situ evaluation of chemotaxis toward fMLP using T1DM rat neutrophils also revealed a deficiency in migration. This impairment in neutrophil chemotaxis was positively related to DM severity which was characterized by glycaemia values greater than 400 mg/dL [47]. In addition, blood neutrophils of diabetic animals presented a decreased migratory response to CXCL2/MIP-2 in vitro and in vivo compared to nondiabetic animals.…”
Section: Impaired Neutrophil Migration In Diabetesmentioning
confidence: 94%